Effect of physical activity on structural asymmetry of mouse hippocampus - T. A. Zapara; A. V. Romashchenko; A. L. Proskura; A. S. Ratushnyak (Вавиловский журнал генетики и селекции)
The relevance of studies of adult neurogenesis is evident in connection with the potential use of these new neurons to replace neurons lost in the process of life. Despite considerable eﬀorts, little is known about the fnal fate of these cells, the functional signifcance of their connections and the regulation of their development. It is known that physical activity signifcantly increases the number of fssile progenitors, the precursors of new neurons in the dentate gyrus of the hippocampus. The existing immunohistochemical methods for labeling new neurons do not allow tracing the temporal dynamics of changes in the volume of brain structures in the same animal, induced by external impacts, such as voluntary exercise. This makes it an urgent task to develop and improve methods for longterm control of changes that occur in the adult hippocampus due to the induction of neurogenesis. The main purpose of this work was to noninvasively track, by using magnetic resonance imaging (MRI), the temporal dynamics of changes in the volume of the hippocampus in the same animals that had voluntary physical activity. It was found that voluntary exercise did not change the total volume of the mouse hippocampus. However, the diﬀerence in the volume ratio between the right and left parts of the hippocampus was signifcantly lower compared with the control group. The reconstruction and analysis of proteinprotein interactions that ensure the survival of a large number of new neurons and their integration into existing neural networks in the hippocampus have been carried out. The proposed approach allows the noninvasive registration of changes in the ratio of the volumes of these paired brain structures.